Hepatoprotective Activity of the Combined Leaf Extracts of Syzygium Polyanthum and Moringa oleifera Against AntituberculosisDrug-Induced Hepatotoxicity in Rats - ELZA SUNDHANI; Galar Sigit Prasuma; Reninta Firda Ramadhani (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Oral antituberculosis drugs (OAT) used repeatedly can negatively impact the liver. Natural compounds with high antioxidant potential could be used as hepatoprotective agents. This study aims to determine the hepatoprotective activity of the combination ethanolic leaf extract of Syzygium polyanthum (SPEE) and Moringa oleifera (MOEE) in rats administered with OAT. The hepatoprotective activity of the combination of SPE and MOE was determined by calculating the SGOT and SGPT levels of rats administered rifampicin (RMP), pyrazinamide (PZA), and isoniazid (INH) for 14 days. An experimental study using eight groups: standard control (CMCM-Na), negative control treatment with OAT (RMP 100 mg/kg BW; PZA: 252 mg/kg BW INH 50 mg/kg BW), positive control (OAT + Curcumin 100 mg/kg BW), OAT+SPEE 150 mg/kg BW group, OAT+MOEE 400 mg/kg BW group, and 3 group OAT + combination SPEE and MOEE (25%: 75%; 50%:50%; 75%:25%). SGPT & SGOT levels were determined using spectrophotometry with analytical methods using specific SGPT & SGOT reagent kits at 340 nm. After 14 days of OAT administration, SGOT levels increased by 1.3-fold, and SGPT levels increased by 1.8-fold compared to baseline levels. This considerable increase is still considered mild hepatotoxicity. The combination of SPEE: MOEE (25%:75%) was most effective in decreasing SGOT levels by 23.5%, or 1.3-fold, whereas the combination treatment of SPEE: MOEE (75%; 25%) was most effective in reducing SGPT levels by 51.56%, or 2-fold. The ratio value of the decrease in SGOT and SGPT levels from single SPEE and MOEE and the combination of both (p>0.05). The combination treatment of SPEE and MOEE in rats administered OAT showed an additive effect and could evolve as a hepatoprotective substance.